Optimizing the Role of Public Administration in Policy and Stunting Reduction Program - Lilisuryani Lilisuryani; Latip Latip; Sabariah Sabariah; Rahmihayati Rahmihayati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Stunting remains a chronic nutritional issue affecting human resource quality in Indonesia, particularly children under five years old. High prevalence of stunting impacts long-term cognitive development, physical growth, and productivity of the young generation (Ministry of Health, 2023). This community service aims to optimize the role of public administration in disseminating policies and programs to reduce stunting through education, training, and direct community assistance. Activities were carried out through coordination with government officials, community health cadres, and local leaders, using local communication media to raise awareness about nutrition. The results indicate an increase in community knowledge on stunting, balanced nutrition practices, and active involvement of both officials and residents in stunting reduction programs. Optimizing public administration through capacity building, cross-sector coordination, and information technology utilization supports program targets. This service recommends strategies for sustainable, participatory, and data-driven program implementation.